Dispatched nurses' experience of wearing full gear personal protective equipment to care for COVID‐19 patients in China—A descriptive qualitative study. Issue 13 (24th March 2021) - Chen, Feifei; Zang, Yuli; Liu, Yuan; Wang, Xiaomin; Lin, Xingfeng
Abstract: Aims and objectives: We explored dispatched nurses' experiences of wearing full gear personal protective equipment to care for patients with coronavirus disease‐2019 (COVID‐19) in Wuhan, China. Background: Full gear personal protective equipment is the primary and foremost measure to prevent the contact and transmission of severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV2); however, working in full gear personal protective equipment may hinder nursing care activities and thus negatively affect patients' and nurses' health. Design: This descriptive qualitative inquiry followed the COREQ guidelines. Methods: Individual semi‐structured telephone interviews were conducted in a purposive sample of 15 frontline nurses who were dispatched to the outbreak epicentre from March to April 2020. Verbatim transcripts were content analysed. Results: Four themes emerged from the data: inadequate preparedness for working with full gear personal protective equipment, full gear personal protective equipment stimulated stress responses, coping strategies and professional growth. Participants learned a great deal from problem‐focussed and emotion‐focussed strategies to tackle challenges related to the prolonged wearing of full gear personal protective equipment for quality nursing care and reduced risk of exposure. They became more vigilant to the adherence to evolving protocols and appropriate training concerning full gear personal protective equipment use. Conclusions: Frontline nurses confronted various but diminishing challenges related to the use of full gear personal protective equipment when caring for patients with COVID‐19 across the approximate 40‐day period. Consistent use of coverall personal protective equipment to protect from SARS‐CoV‐2 in high exposure settings would be feasible if nurses were better prepared; therefore, scenario‐based skill training concerning the prolonged use of full gear personal protective equipment should be offered regularly and intensively. Relevance to clinical practice: This study informs future decisions concerning improved full gear personal protective equipment‐related psychomotor training and promoting ways for nurses to cope with the stress that comes from working in highly contiguous environments.